ECONOMIC ANALYSIS OF CATTLE MARKETING AND RISKS AMONG TRADERS IN NORTH-CENTRAL NIGERIA - A. Atser, Emmanuel; T. G. Ashiko , Dr. Felix; Atagher , Dr. M. M.; Hanmaikyur, Dr. T. J. (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
The study analyzed cattle marketing and risks among traders in North-Central Nigeria. It considered the socio-economic characteristics of cattle marketers, Primary data were collected from 350 market intermediaries using stratified sampling techniques. The methods of data analysis included descriptive statistics such as frequency distribution tables, mean and percentages. Results revealed that for objective one, cattle marketing is male dominated as 100% of market intermediaries were males. Age was also a significant positive attribute of cattle marketing which revealed that 64.3% of respondents were less than 50 years, hence physically capable of undertaking the business. Findings of objective two revealed three types of intermediaries who were found to be very important in cattle marketing in the study area. These included wholesalers, retailers and brokers. Result of objective three of the study indicates that there was no fixed cost item because traders did not own either a warehouse or a truck. Most of their expenses were restricted to the operational costs of maintaining the animals in terms of supplementary feeding before final conveyance to the distant markets as well as taxes/levies paid in transit and thus only gross margin could be calculated. The researcher concluded that cattle marketing in North-Central Nigeria was profitable despite that wholesalers incurred the high costs, followed by retailers and brokers, largely from transportation cost. The study recommended among others that credit institutions should support cattle marketing, illegal taxes and levies on cattle marketing should be eliminated while on transit as well as provision of good and affordable transport system.